Optical properties of a thin layer of the Vanadium dioxide at the metal state - Benchaib, Abderrahim; Mdaa, Abdesselam; Zorkani, Izeddine; Jorio, Anouar (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The vanadium dioxide VO? currently became very motivating for the nanotechnologies’ researchers. It makes party of the intelligent materials because these optical properties abruptly change semiconductor state with metal at a critical temperature ? = 68 °C. This transition from reversible phase is carried out from a monoclinical structure characterizing its semiconductor state at low temperature towards the metal state of this material which becomes tétragonal rutile for ? > 68°????; it is done during a few nanoseconds. Several studies were made on this material in a massive state and a thin layer. We will simulate by Maple the constant optics of a thin layer of VO? thickness z = 82 nm for the metal state according to the energy ? of the incidental photons in the energy interval: 0.001242 ? ? (ev) ? 6, from the infra-red (I.R) to the ultra-violet (U.V) so as to be able to control the various technological nano applications, like the detectors I.R or the U.V, the intelligent windows to increase the energy efficiency in the buildings in order to save the cost of energy consumption by electric air-conditioning and the paintings containing nano crystals of this material. The constant optics, which we will simulate, is: the index of refraction, the reflectivity, the transmittivity, the coefficient of extinction, the dielectric functions ?1 real part and ?2 imaginary part of the permittivity complexes ? of this material and the coefficient absorption.